Secure routing using frequency hopping in wireless sensor network - Raja Mohd. Radzi, Raja Zahilah (2007)
Wireless ad hoc sensor networks (WSN) operate in the absence of a pre-deployed infrastructure, are self-configurable, low cost and can be rapidly deployed. Hence, such networks enable a variety of consumer applications, such as emergency rescue, disaster relief, smart homes and patient monitoring, industrial applications, such as structural health monitoring and environmental control, and military applications, such as target identification and tracking. WSN are prone to failure and malicious user attack because any device within the frequency range can get access to the data being transmitted. Thus, the project aims to provide a secure WSN through frequency hopping at the network layer. In this work, Ad hoc On Demand Distance Vector Routing algorithm is used to determine the route and un-Slotted Carrier Sense Multiple Access / Collision Avoidance (slotted CSMA/CA) algorithm is used to access the medium. The frequency hopping algorithm was tested in WSN environment with and without malicious node. The results show tremendous decreased of throughput from malicious node when the number of frequency hop is increased. Therefore, WSN’s security is improved even though the throughput from source is slightly decreased. Proposed future works are addition of frequency synchronization with beacon using slotted CSMA-CA and addition of multiple interfaces support for IEEE 802.15.4 standard.